1999
DOI: 10.1038/sj/pcan/4500294
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis for prostate biopsy: benefits and costs

Abstract: Transrectal ultrasound-guided core biopsy is a widely used method to diagnose prostate cancer. It is generally considered a safe procedure but the main concern is that signi®cant complications such as infections do occur. To evaluate the effect of a combined two-dosage antibiotic prophylaxis with cipro¯oxacin and metronidazole, a prospective study of 289 patients undergoing core-biopsy of the prostate was performed. Five patients (1.7%) developed urinary tract infection and all did recover without any further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Recently, it was reported that there is no clinical or statistical difference between the 1-day and 3-day antibiotic prophylaxis regimen for patients undergoing TRUS-guided prostate biopsy [20]. Larsson et al [21] concluded that no prophylactic therapy was considered good.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that there is no clinical or statistical difference between the 1-day and 3-day antibiotic prophylaxis regimen for patients undergoing TRUS-guided prostate biopsy [20]. Larsson et al [21] concluded that no prophylactic therapy was considered good.…”
Section: Discussionmentioning
confidence: 99%
“…The role of antimicrobial prophylaxis for preventing infections after TRUS‐guided prostate biopsy (TGB) is well established [1,2]. Although a wide variety of antimicrobial regimes has been suggested, fluoroquinolones are the most commonly used antimicrobials for prophylaxis for these procedures [3].…”
Section: Introductionmentioning
confidence: 99%
“…The cost of biopsy and the cost of management of biopsy complications were assumed to be $150 and $500, respectively, as reported by Ellison et al 16 . and Larsson et al 17 . The sensitivity and specificity of conventional PSA were assumed to be 0.95 and 0.10, respectively, based on an excellent review by Roddam et al 6 .…”
Section: Methodsmentioning
confidence: 99%
“…Carey et al 15 The cost of biopsy and the cost of management of biopsy complications were assumed to be $150 and $500, respectively, as reported by Ellison et al 16 and Larsson et al 17 The sensitivity and specificity of conventional PSA were assumed to be 0.95 and 0.10, respectively, based on an excellent review by Roddam et al 6 The prevalence of prostate cancer was assumed to be 0.03 in Thompson's reports 18,19 in addition to the reports on prostate cancer screening programs worldwide (Table 1). In the decision tree model, the probability of a positive primary screening test (Ppositive primary screening test) was calculated as:…”
Section: Andmentioning
confidence: 99%